Novel strategies for the management of vancomycin-resistant enterococcal infections (2019)
Purpose of review: Vancomycin-resistant enterococci (VRE) are important nosocomial pathogens that commonly affect critically ill patients. VRE have a remarkable genetic plasticity allowing them to acquire genes associated with antimicrobial resistance. Therefore, the treatment of deep-seated infections due to VRE has become a challenge for the clinician. The purpose of this review is to assess the current and future strategies for the management of recalcitrant deep-seated VRE infections and efforts for infection control in the hospital setting. Recent findings: Preventing colonization and decolonization of multidrug-resistant bacteria are becoming the most promising novel strategies to control and eradicate VRE from the hospital environment. Fecal microbiota transplantation (FMT) has shown remarkable results on treating colonization and infection due to Clostridiodes difficille and VRE, as well as to recover the integrity of the gut microbiota under antibiotic pressure. Initial reports have shown the efficacy of FMT on reestablishing patient microbiota diversity in the gut and reducing the dominance of VRE in the gastrointestinal tract. In addition, the use of bacteriophages may be a promising strategy in eradicating VRE from the gut of patients. Until these strategies become widely available in the hospital setting, the implementation of infection control measures and stewardship programs are paramount for the control of this pathogen and each program should provide recommendations for the proper use of antibiotics and develop strategies that help to detect populations at risk of VRE colonization, prevent and control nosocomial transmission of VRE, and develop educational programs for all healthcare workers addressing the epidemiology of VRE and the potential impact of these pathogens on the cost and outcomes of patients. In terms of antibiotic strategies, daptomycin has become the standard of care for the management of deep-seated infections due to VRE. However, recent evidence indicates that the efficacy of this antibiotic is limited, and higher (10-12 mg/kg) doses and/or combination with β-lactams is needed for therapeutic success. Clinical data to support the best use of daptomycin against VRE are urgently needed. This review provides an overview of recent developments regarding the prevention, treatment, control, and eradication of VRE in the hospital setting. We aim to provide an update of the most recent therapeutic strategies to treat deep-seated infections due to VRE.